Ecological vulnerability assessment based on remote sensing ecological index (RSEI): A case of Zhongxian County, Chongqing - Lan, Guoxin; Jiang, Xiaolan; Xu, Denghui; Guo, Xianhua; Wu, Yan; Liu, Yixuan; Yang, Yuzheng (Frontiers in Environmental Science, 2023)
The ecological vulnerability evaluation index was established through Normalized Difference Vegetation Index (NDVI), Wetness (WET), Normalized Difference Build-up and Soil Index (NDBSI) and Land Surface Temperature (LST) indicators, comprehensively evaluate the ecological vulnerability of Zhongxian County of Chongqing in 2002, 2009, and 2016 by Principal Components Analysis (PCA), and analyze its spatio-temporal evolution. The vulnerability areas of five levels were calculated respectively, and the overall index of ecological vulnerability was also calculated. The index of remote sensing ecological index (RSEI) and Normalized Difference Vegetation Index decreased first and then increased; the Wetness index showed an upward trend; the Normalized Difference Build-up and Soil Index index increased first and then decreased; and the Land Surface Temperature index decreased. The ecological vulnerability body index (EVBI) shows a downward trend, and the incremental changes are mainly concentrated in the negligible vulnerability areas and light vulnerability area, while the medium vulnerability, strong vulnerability and extreme vulnerability area generally show a downward trend. Furthermore, the new increment of ecological vulnerability grade area concentrates on negligible vulnerability area and light vulnerability area from 2002 to 2016. In general, the ecological vulnerability gradually shifts to low vulnerability, and the ecological environment tends to develop healthily.